2006
DOI: 10.1523/jneurosci.3859-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Differentiation and DNA Binding (Ids) Regulate Math1 and Hair Cell Formation during the Development of the Organ of Corti

Abstract: The basic helix-loop-helix (bHLH) transcription factor Math1 (also calledAtoh1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 55 publications
10
127
1
Order By: Relevance
“…All the auditory and vestibular hair cells were absent in Atoh1 deficient mice, 2 4 and ectopic re-introduction of wild-type Atoh1 restored the hair cell fate within both the pro-sensory domain and non-sensory regions of the cochlea. 25 In line with these observations, our data demonstrated that Celastrol enhanced neuronal-like cell identity in the inner ear stem cell population as well as their electrophysiological function, which was highly likely to be mediated by the up-regulation of Atoh1. In addition to preservation and stimulation of the regeneration capacity, here we provided evidences that Celastrol treatment also enhanced the differentiation of inner ear stem cells into neuronal-like cells, and their electrophysiological functioning.…”
Section: Discussionsupporting
confidence: 86%
“…All the auditory and vestibular hair cells were absent in Atoh1 deficient mice, 2 4 and ectopic re-introduction of wild-type Atoh1 restored the hair cell fate within both the pro-sensory domain and non-sensory regions of the cochlea. 25 In line with these observations, our data demonstrated that Celastrol enhanced neuronal-like cell identity in the inner ear stem cell population as well as their electrophysiological function, which was highly likely to be mediated by the up-regulation of Atoh1. In addition to preservation and stimulation of the regeneration capacity, here we provided evidences that Celastrol treatment also enhanced the differentiation of inner ear stem cells into neuronal-like cells, and their electrophysiological functioning.…”
Section: Discussionsupporting
confidence: 86%
“…4A). Inhibitors of differentiation and DNA binding (Ids) 1, 2, and 3 all negatively regulate Atoh1 by competitive-binding to E proteins (Connerney et al 2006;Jones et al 2006) (Fig. 4B).…”
Section: Post-translational Regulationmentioning
confidence: 99%
“…Western blot analyses carried out by the manufacturer on murine samples have demonstrated that this antibody, as well as the anti-Jagged1 (C-20) antibody discussed below, does not cross-react and recognizes a single protein of the correct size (150 kDa molecular weight). Others have used the H-114 antibody in mouse inner ear (Zine and de Ribaupierre 2002;Woods et al 2004;Kiernan et al 2006;Jones et al 2006). Jagged1 is an affinity purified goat polyclonal antibody raised against the C-terminus of human Jagged1.…”
Section: Antibodiesmentioning
confidence: 99%
“…Jagged1 is expressed in embryonic SCs in mouse organ of Corti, but its expression in the adult ear is unknown (Zine and de Ribaupierre 2002;Woods et al 2004;Brooker et al 2006;Jones et al 2006;Murata et al 2006). Because of its presence in developing SCs, we examined its expression in normal and drugdamaged adult ears.…”
Section: Normalsmentioning
confidence: 99%